Martin Luther - Harrison, Cassian; West, Timothy; Neeson, Liam.; Powell, Nick.; Lion Television Ltd.; Public Broadcasting Service (U.S.); Devillier-Donegan Enterprises; PBS DVD Video; Warner Home Video (Firm) ([Alexandria, Va.] : PBS DVD Video ; Burbank, CA : Distributed by Warner Home Video, 2003)
Martin Luther nailed his treatise to the doors of the Wittenberg Cathedral and forever changed the Christian world. This previously obscure German monk unleashed forces that would plunge Europe into war and chaos. He offered the Christian world a new vision of man's relationship with God and, in turn, redefined man's relationship with authority in general, bringing the collapse of the medieval world and the birth of the modern age.
Pt. 1. Luther's last journey ; A child of the church ; To house and school ; Plague and crisis ; Life in the monastery ; The journey to Rome ; The indulgence crisis -- pt. 2. The ire of Rome ; Raising the stakes ; The Protestant manifesto ; The diet of worms ; Confusion and exile ; Reformation ; The legacy.
DVD.
Special features: interview extras: "Luther the hero", "Luther the villain", "Luther's world"; behind the scenes.
"An Empires special."
Videodisc release of a 2002 television program.
"Presented in a 'matted' widescreen format preserving the aspect ratio of its original theatrical exhibition. Enhanced for widescreen TVs"--Container.
Recorded in Dolby surround stereo.
Keywords: Luther, Martin, -- 1483-1546.; Reformation -- Germany; Monks -- Germany; Biographical television programs; Feature films; Documentary films